2018
DOI: 10.1063/1.4997059
|View full text |Cite
|
Sign up to set email alerts
|

Coherence analysis of a class of weighted networks

Abstract: This paper investigates consensus dynamics in a dynamical system with additive stochastic disturbances that is characterized as network coherence by using the Laplacian spectrum. We introduce a class of weighted networks based on a complete graph and investigate the first- and second-order network coherence quantifying as the sum and square sum of reciprocals of all nonzero Laplacian eigenvalues. First, the recursive relationship of its eigenvalues at two successive generations of Laplacian matrix is deduced. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Existing studies have demonstrated that calculations of the Laplacian eigenvalues face an enormous challenge because the eigenvalues are dominated by the network topology [9][10][11]. It is of interest to explore diverse methods to reveal the correlation between the topology and the coherence [12,13]. Particularly, for some fractal networks [14,15], such as Koch networks [16], Vicsek fractals [1], Sierpiński graphs [17], are all good candidate network models to derive an exact scaling of network coherence regarding the network size.…”
Section: Introductionmentioning
confidence: 99%
“…Existing studies have demonstrated that calculations of the Laplacian eigenvalues face an enormous challenge because the eigenvalues are dominated by the network topology [9][10][11]. It is of interest to explore diverse methods to reveal the correlation between the topology and the coherence [12,13]. Particularly, for some fractal networks [14,15], such as Koch networks [16], Vicsek fractals [1], Sierpiński graphs [17], are all good candidate network models to derive an exact scaling of network coherence regarding the network size.…”
Section: Introductionmentioning
confidence: 99%
“…In [10], Hong et al investigated a relation between the coherence and the number of initial nodes and showed the consensus bears better with a smaller number of initial nodes. Dai et al obtained the scalings of first-and second-order coherence for a family of weighted networks and found that the scalings obey different laws with a range of weight factors [11].…”
Section: Introductionmentioning
confidence: 99%
“…This concept of the network coherence helps to study the relationship between the Laplacian eigenvalues and network consistency. Great progress has been made for some special networks such as Vicsek fractals [10], tree-like networks [11], Sierpiński graphs [18] and weighted networks [19]. Many works have been devoted to studying the network coherence.…”
Section: Introductionmentioning
confidence: 99%